Alleviate the J–V hysteresis of carbon-based perovskite solar cells via introducing additional methylammonium chloride into MAPbI3 precursor. Issue 61 (15th October 2018) - Jiang, Huirong; Liu, Xingyu; Chai, Nianyao; Huang, Fuzhi; Peng, Yong; Zhong, Jie; Zhang, Qi; Ku, Zhiliang; Cheng, Yi-bing
Abstract : The hysteretic phenomenon commonly exists in the J – V curves of perovskite solar cells with different structures, especially for carbon-based mesoscopic perovskite solar cells without hole-conductor (carbon-based PSCs). Abstract : The hysteretic phenomenon commonly exists in the J – V curves of perovskite solar cells with different structures, especially for carbon-based mesoscopic perovskite solar cells without hole-conductor (carbon-based PSCs). By adding moderate amounts of methylammonium chloride (MACl) into MAPbI3 perovskite precursor, we found the J – V hysteresis of carbon-based PSCs could be significantly alleviated and the crystallinity of MAPbI3 perovskite could also be influenced. With the increasing amount of MACl, MAPbI3 perovskite showed better and better crystallinity until the MACl came to 0.45 M. The champion device with 0.45 M of additional MACl exhibited a preferable PCE of 14.27% for reverse-scan (RS) and 14.50% for forward-scan (FS), significantly higher than that of the pristine device (8.74% for RS and 4.80% for FS). What's more, the J – V hysteretic index of the device gradually decreased along with the increasing amount of MACl, and kept at low value even when the crystallinity of MAPbI3 perovskite became poor. Through XRD and PL analysis, we demonstrated that the recombination rate of the accumulated charges at the perovskite/TiO2 interface is the main reason for photocurrent hysteresis in carbon-based PSCs. High quality of perovskite crystals is an important contributing factor for high-performance PSCs with low hysteresis, but there is no necessary correlation between low hysteresis and good crystallinity. This research presents an effective way to fabricate carbon-based PSCs with low-hysteresis, and at the same time, provides evidence for investigating the origin of J – V hysteresis of PSCs.